Utility of T-cell immunosequencing in distinguishing mycosis fungoides progression from treatment related cutaneous adverse events - Bhatti, Safiyyah; Joffe, Daniel; Banner, Lauren; Talasila, Sahithi; Mandel, Jenna; Lee, Jason; Porcu, Pierluigi; Nikbakht, Neda (Frontiers in Medicine, 2023)
Cutaneous adverse events to both topical and systemic drugs in patients with mycosis fungoides (MF) present a diagnostic challenge as it is often difficult to distinguish drug associated rash from disease progression in the skin. Mogamulizumab and mechlorethamine gel are approved treatments for MF, both of which can cause treatment related cutaneous adverse events. It can often be challenging to distinguish mogamulizumab associated rash (MAR) and mechlorethamine gel associated hypersensitivity dermatitis from MF progression both clinically and histologically. High-throughput sequencing (HTS) of the T-cell receptor (TCR) can be used to assess T-cell clonality to support a diagnosis of MF. After identification of the malignant TCR clone at baseline, HTS can track the established malignant TCR sequence over time with high sensitivity. As a result, HTS clone tracking can aid in distinguishing disease progression from treatment side effects. Here, we present a case series to demonstrate how monitoring of the malignant T-cells by HTS can aid in diagnosis of mogamulizumab and mechlorethamine gel cutaneous adverse events.